Asian Christianity and Religious Pluralism - Gnanaraja, D.X. (University of jaffna, 2024)
Afghanistan, Pakistan, Maldives and Bangladesh in the SAAR where Islam is the State Religion; India, Sri Lanka, Nepal and Myanmar are secular as per their constitution. In Bhutan Buddhism is the State Religion. This is the context the role of Christianity as community builder among different faiths. Percentage of Christians in South Asian nations: Bangladesh:0.5%; Bhutan:0.9%; India: 2.7%; Maldives: no figures available; Nepal: 1%; Pakistan: 1.6%; Sri Lanka:7.5%. Today Christians are found in all the South Asian countries. Leadership of the churches is in the hands of the local people, who continue to wrestle with the big issues of the sub-continent: inequality and religious pluralism. How do Christ’s followers work out his message both in caring for individuals and also engaging with social and economic structures? How do they express their faith through their South Asian culture, in the context of many other religions? Many South Asians react in the negative way. It’s not surprising that they conclude that while Jesus may be OK, his followers are not always that great. That’s why some Christians prefer to call themselves ‘followers of Christ’. They don’t want to identify their faith with one particular culture but want to emphasise the relationship with Jesus Christ, rather than cultural and institutional structures, which can be misleading. It is seen that the average of Christians in the region is less than 3 percent yet it has done yeomen service to the countries wherever it is spread. The benefits of Christianity can be assessed only by their educational institutions on the region. Barring Afghanistan, all other countries have the Christian schools particularly for girl children. This is the aspect I want to highlight in the study. Like – the leaven Matthew 13.33 Luke 13:20, the Christian community though as small as a mustard seed, when grows to great institutions of learning.
Keywords: Religious pluralism; Christian minorities; Educational contribution